THE EFFECT OF INNOVATION SKILL AND ENGAGED BEHAVIOR ON MEDICAL REPRESENTATIVE PERFORMANCE AND ITS IMPACT ON ACHIEVEMENT OF SALES TARGETS PT OPI AREA BEKASI, CIKARANG, KARAWANG - Dinarsasi Dinarsasi; Sampurno A Chaliq; Derriawan Derriawan (Jurnal Ekonomi, 2023)
The high level of competition in the pharmaceutical industry that demands to be at the forefront, fastest and best in meeting customer needs, this cannot be separated from the function of the marketing department in the pharmaceutical industry itself to implement marketing strategies that are in accordance with the situation and conditions of the pharmaceutical market. The purpose of this study is the effect of innovation skills and engaged behavior on the performance of medical representatives and their impact on achieving sales targets for PT OPI in the Bekasi area, Cikarang, Karawang. The research method used in this research is quantitative research using SEMPLS. The results of the analysis show that Innovation skills have a positive effect on the performance of Medical Representatives, Engaged behavior has a positive effect on the performance of Medical Representatives, Innovation skills have a positive effect on achieving sales targets for Medical Representatives, Engaged behavior has a positive effect on achieving sales targets for Medical Representatives and Performance of Medical Representatives has a positive effect with the achievement of the sales target of PT OPI.